Pegasus - Matthew Knox (Oz, 1988)
It is the poetry of standing atop an isolated Kansas hill with the sun and the wind, along with the beauty of the view, sitting thousands of feet above the plains from an airplane that has drawn Pegasus ... a school to fly .. . a place for being ... a place for meaning...